Metacognition and cooperative learning based on deliberative democracy moderated by learning style toward critical thinking skill in social studies learning - Agus Suprijono; Ersis Warmansyah Abbas; Riyadi (Cogent Education)
This research investigated the influence of metacognition and cooperative learning based on deliberative democracy on students’ critical thinking skills in social studies learning, focusing on how learning style moderated this relationship. The study employed a quantitative research approach utilizing moderated regression analysis to examine the direct effect of the educational intervention and the moderating effect of learning style. Data were collected from 35 junior high school students using validated questionnaires measuring metacognition, cooperative learning, learning style, and critical thinking. The findings revealed that metacognition and cooperative learning significantly enhanced students’ critical thinking skills. Learning styles significantly moderated the relationship between cooperative learning and critical thinking skills. Notably, integrating metacognitive strategies and cooperative learning approaches grounded in the principles of deliberative democracy significantly impacted the development of students’ critical thinking skills in social studies learning.